2008
DOI: 10.1007/s11095-008-9593-4
|View full text |Cite
|
Sign up to set email alerts
|

ATR/Raman and Fractal Characterization of HPBCD/Progesterone Complex Solid Particles

Abstract: - mu-FT-IR, mu-Raman and X-ray spectroscopy, and the dissolution test did not reveal defined differences among the three different types of particles, confirming occurrence of the complex in the solid state. The spherical shape, the very small size and the low value of the contour fractal dimension allows better technological performance of the particles obtained by spray-drying: this drying process appears the most promising one to prepare dry particles of the HPBCD/P complex, in view of its formulation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
2
12
0
2
Order By: Relevance
“…The Raman spectrum of the DDP standard exhibited sharp characteristic peaks between 1600 and 1700 cm , which could be attributed to the carbon-carbon double bond and carbonyl stretching vibration of the steroidal backbone. 26) These peaks coincided with those of the observed crystals in GP and GM; therefore, the observed crystals in GP and GM were identified as DDP. Refai and Muller-Goymann reported that changes in steroid permeation are dependent on the concentration of dissolved corticosteroid in the vehicle.…”
Section: Resultssupporting
confidence: 65%
“…The Raman spectrum of the DDP standard exhibited sharp characteristic peaks between 1600 and 1700 cm , which could be attributed to the carbon-carbon double bond and carbonyl stretching vibration of the steroidal backbone. 26) These peaks coincided with those of the observed crystals in GP and GM; therefore, the observed crystals in GP and GM were identified as DDP. Refai and Muller-Goymann reported that changes in steroid permeation are dependent on the concentration of dissolved corticosteroid in the vehicle.…”
Section: Resultssupporting
confidence: 65%
“…Em especial, as bandas características do OEC em 2835, 1639, 1611 e 1510 cm -1 tiveram uma acentuada redução de intensidade comparada aos espectros isolados do OEC e da MF, sugerindo que estas ligações possivelmente estão implicadas na formação destes complexos, visto que a inserção de uma molécula-hóspede no interior da cavidade da b-CD provoca uma restrição conformacional, reduzindo a livre movimentação das moléculas encapsuladas, reduzindo a intensidade do sinal. Esse mesmo efeito foi percebido por Fini, 39 Oliveira, 33 e Rocha 31 quando prepararam complexos de inclusão utilizando a b-CD. Além destes efeitos, observou-se ainda o deslocamento das bandas de estiramento OH da b-CD em 3346 cm -1 para 3338 cm -1 no CI e da banda de estiramento C -H da b-CD em 2928 cm -1 para 2919 cm -1 no CI, reforçando a teoria da formação do complexo de inclusão.…”
Section: Espectroscopia De Infravermelhounclassified
“…In the spectrum of pure progesterone (Fig. 4(a)), there are two sharp and well-resolved bands at 1662 cm −1 (ν 1 (C=O)) and 1698 cm −1 (ν 2 (C=O)) assigned to carbonylstretching bands of C 3 and C 20 , respectively, and a lessintensive band at 1615 cm −1 corresponding to the stretching vibration band of C=C (54)(55)(56).…”
Section: Ftir Spectroscopymentioning
confidence: 99%